Islamic Jurisprudence for Diversity: From Theological-Normative Reason to Progressive Contextual Reasoning - Naim, Ngainun (al-'adalah, 2018)
The reality of Indonesian society is a multicultural society. Therefore, religious understanding and toleration to differences and diversity is necessary to be developed in order to create peace and harmony in the social life. This paper aims to explore the concept of Islamic Jurisprudence in the context of social diversity. This concept is important because the old fiqh concept resting on normative-theological reasonings needs to be reconstructed and replaced with contextual-progressive ones. The changes in the fiqh epistemology from normative-theological to contextual-progressive reasonings are carried out through adaptation to principles of Maqâshid al-Sharîah (basic aims of religious provisions) which are contextualized according to the social growth. The new model of fiqh constructed through combination of religious teachings and social development is expected to make a valuable contribution to the establishment of peace and harmony among all elements of Indonesia society.